Solve for z 2z-6=-12

Math
2z-6=-12
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Add 6 to both sides of the equation.
2z=-12+6
Add -12 and 6.
2z=-6
2z=-6
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2z=-6 by 2.
2z2=-62
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2z2=-62
Divide z by 1.
z=-62
z=-62
Divide -6 by 2.
z=-3
z=-3
Solve for z 2z-6=-12

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top